Approach towards validity of Aggressive Packet Combining Scheme with Physical Level Representation - Sarkar, Achyuth; Chakraborty, SK; Bhunia, CT; Chakrabarti, Prasun (International Journal of Computer Sciences and Engineering, 2025)
It is a research challenge for scientists and researchers to reliably transport data from source to destination. The received copies were found to be loaded with errors and the recovery of the correct original copy was a challenging job. The paper deals with some novel protocols related to physical level representation, circular shift based information transmission, masking scheme and modified packet combining technique through with this problem can be addressed to a considerable extent.